2018
DOI: 10.1002/adem.201800753
|View full text |Cite
|
Sign up to set email alerts
|

Inert Gas Atomization of High‐Nitrogen TRIP‐Steels

Abstract: High nitrogen steels with transformation induced plasticity (TRIP) effect have been recently developed within the framework of the project CRC799. These steels are utilized in a form of powder for the needs of this project. Therefore, the current study focuses on the powder production of high nitrogen steels via inert gas atomization process. Specifically, the role of nitrogen content in determination of the basic powder properties and its behavior on the atomization process are investigated. Additionally, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Surprisingly, simultaneous modification of ST and viscosity did not surpass the individual change of either ST or viscosity. From the previous work [15], it is known that formation of the frozen metal "crown" on the ceramic nozzle during the spraying may significantly affect the dynamic of metal flow rate from the tundish. In addition, during crown formation, the cone of gas jet should be distorted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, simultaneous modification of ST and viscosity did not surpass the individual change of either ST or viscosity. From the previous work [15], it is known that formation of the frozen metal "crown" on the ceramic nozzle during the spraying may significantly affect the dynamic of metal flow rate from the tundish. In addition, during crown formation, the cone of gas jet should be distorted.…”
Section: Resultsmentioning
confidence: 99%
“…Atomizations of the metal samples were executed in the inert gas atomization unit VIGA-1B (supplied by ALD Vacuum Technologies) ( Figure 2). A detailed description of the unit can be found in previous publications [15,16]. The atomizer consists of two vacuum-tight steel chambers.…”
Section: Methodsmentioning
confidence: 99%
“…Examining obtained PSD values, manufactured powders remain in a range of typical values for this atomization unit under comparison to previously published works. [45,46] Korobeinikov et al [46] reported that d50 decreases by enhancing of the spraying temperature and decrease in the spraying rate. Nevertheless, these tendencies are not fully realized in the current study.…”
Section: Powder Size Distribution and Particles Morphologymentioning
confidence: 99%